Peningkatan Hasil Belajar Siswa Dengan Menggunakan Model Problem Based Learning Pada Mata Pelajaran PAI di Kelas IV UPTD SDN 05 Muaro Paiti - Hidayati Sadli; Syawaluddin Syawaluddin; Deslita Deslita; Dila Yanti Safitri; Yeni Susila; Delfiyanti Delfiyanti (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This study aims to improve the learning outcomes of fourth grade students in Islamic Religious Education (PAI) subjects at UPTD SDN 05 Muaro Paiti through the application of the Problem Based Learning (PBL) learning model. The PBL model was chosen because it is considered capable of activating students in learning and solving problems actively. This research is class action research conducted in 4 cycles. In each cycle, there are stages of planning, implementation, observation, and reflection. The instruments used in this study were learning outcome tests and student activity observation sheets. The results showed that there was a significant increase in student learning outcomes after the implementation of the PBL model. In the initial data, the percentage of students who achieved KKTP was still low. However, in cycles I, II, III, and IV the percentage of students who achieved KKTP always increased significantly. This shows that the PBL model is effective in improving student learning outcomes in PAI subjects. In addition, observations of student activities showed a significant increase in each cycle. Students became more active, critical, and creative in solving the problems given. Thus, it can be concluded that the PBL model can be an effective alternative learning model to improve student learning outcomes in PAI subjects.